Latin America, the Caribbean and the OECD : a dialogue on economic reality and policy options - Maddison, Angus, ed. (OECD. Development Centre ParisFR, 1986)
Compares economic performance and policy in Latin American and OECD countries between 1938 and 1985. Discusses development and crisis in Latin America 1950-84. Examines prospects for global growth open to Latin America in the long run and the requirements for ensuring such growth. Gives an economic overview of the Caribbean discussing the Caribbean Development and Cooperation Committee, the external relations of the Caribbean and its policies for the future. Discusses economic development and crisis in Central America, the dynamics of world trade and a possible international solution to the debt problem.